Participação social em educação e dominação: uma análise sobre o campo e as implicações do trabalho parrésico - Batista, José Ricardo (2021)
The discourse about the democracy participation in education asks educators, for instance. This paper on the assumption that the policies actives take on important in all human life, especially, from the participative democracy model. Therefore, we seek to investigate how the mechanisms of social participation in educational public policies have been developed, purposing to understand the resignifies and establish regimes of truths grounded by the speeches. We used dice from official documents, laws among others. In addition to treating parrhesic work as a possibility for the present day, from the perspective of resistance to the governmentalized state. Besed on a theoretical basis in Michel Foucault, we sought to understand the dynamics established by the governmentality that uses institutions, as well as the structures proper to the Democratic State to constitute a homogeneous group that reinforce and expand its Power. One of the sides, which is the parrhesic represent the rupture of that order. It suggesting think that we have ethical experiences that overcome all harassment of normalizing devices. The, we rake up some implications of Foucault's analysis are evaluated to rethink the dilemmas of educational theorization and the role of teachers and education professionals as intellectuals to specific rationality developed today. Consciousness and this practice originated by the antiquity, implies a virtue, a quality and a duty that in the political and educational show as a technique of your own direction. Because of that, this paper examined official documents and some bibliographic references to understand how this transition takes place between intellectual discussion and the formation of a set of laws, projects, opinions, theses and pedagogical / legislative proposals with the scope of unifying thought and that provides the improvement of governmentality. Freedom is a fundamental principle of democracy. For that reason, any form of limitation, restraint and weakening must be repelled by anyone. The centralization at the state level represents a serious threat to freedom. In our reality, we can note a strong centralization. This can make easy the implementation of totalitarianism. Only the strengthening of the individual as an autonomous being can represent a way of resisting governmentality. In the end, we’d like to talk about the role of education in this scheme that we will try to situate in this characteristic game of modernity.